Studying the Effect of Noise Barrier Characteristics on Traffic Noise in Urban Areas - Ramadan Ibrahim; Salah Tahra; Alhariri Osama (Civil and Environmental Engineering)
This research aims to identify the optimal noise concrete barrier mix through two critical stages. The initial step involves calibrating a traffic noise model via a field survey at 18 locations, encompassing volume counts and noise levels at varying distances. The subsequent step entails laboratory tests on different concrete barrier materials. The researchers developed two regression models. In the laboratory, they investigated five barrier types: reinforced, three variations of foamed concrete, and foamed concrete without aggregate. Employing a 92 dB noise source, they measured noise levels at distinct distances from the barrier. Ultimately, foamed concrete without aggregate emerged as the most effective barrier, potentially reducing noise levels by up to 46.4% at a distance of 3 meters with the use of this barrier.